DEVELOPMENT OF DEEP LEARNING-BASED TEACHING MODULES IN MATHEMATICS FOR GRADE VI STUDENTS - Kristian Putri, Tania Diar; Kartika Chrysti Suryandari; Septi Yulisetiani (Universitas Islam Negeri Mataram, 2026)
This study was conducted to identify the shortcomings of learning tools that have not been widely used at the elementary school level. These limitations motivated educators to develop learning tools in the form of animated learning modules that engage students' interest, particularly in the mathematics subject